A highly practical and convenient halogenation of fused heterocyclic N-oxides. Issue 38 (22nd September 2016) - Wang, Dong; Wang, Yuxi; Zhao, Junjie; Li, Linna; Miao, Longfei; Wang, Dong; Sun, Hua; Yu, Peng
Abstract: A novel, simple and practical method for the regioselective halogenation of fused heterocyclic N -oxides has been developed. It employs Vilsmeier reagent, generated in situ by POX3 and DMF, as both the activating agent and the nucleophilic halide source. The method is amenable across a broad range of substrates, including quinolines, isoquinolines and the diazine N -oxides, possessing a variety of substitution patterns. Furthermore, all of the reagents associated are cheap and easy to obtain. The potential extension of this method to a one-pot oxidation/halogenation sequence that obviates the need for isolation of the N -oxide intermediates is also presented. Graphical abstract: A novel, mild and practical method for the regioselective halogenation of fused azine N -oxides and diazine N -oxides has been developed. The procedure is operationally simple, compatible with a broad range of functional groups, and all of the reagents associated are cheap and easy to obtain. The potential extension of this method to a one-pot oxidation/bromination sequence that obviates the need for isolation of the N -oxide intermediates is also presented.